Quantitative easing and sovereign yield spreads : Euro-Area time-varying evidence - Afonso, António (2018)
We assess the determinants of sovereign bond yield spreads in the period 1999-2016, considering non-conventional monetary policy measures in the Euro area. We use a 2-step approach: i) confirm (by means of model selection methods) and estimate (by means of panel techniques) the determinants of sovereign bond yield spreads; ii) compute bivariate time-varying coefficient (TVC) models of each determinant on government bond spreads and analyse the temporal dynamics of resulting estimates. Our results show that the baseline determinants of sovereign bond yield spreads in the Euro area are the bid-ask spread, the VIX, fiscal developments and rating developments, REER, and economic growth. In recent years, additional relevant determinants became the QE measures implemented by the ECB in the aftermath of the economic and financial crisis. From the TVC analysis, the Covered Bond Purchase Programme contributed to reduce yield spreads in all Euro area countries in the analysis, particularly in the crisis period, 2011-2013. In addition, longer-term refinancing operations contributed to reduce yield spreads in most countries.